ANALISIS KONTRASTIF KLAUSA PASIF BAHASA INDONESIA DAN BAHASA SUNDA : TINJAUAN MORFOSINTAKSIS - Nani Darheni (Jurnal Sosioteknologi, 2010)
In the Indonesian language have been found three type of the passive sentence, that is, the canonical passive, the passive which has the surface from of on object topicalization, and the other type. Even though, in the Indonesian language only has two type of the passive sentence, that is, the canonical passive and the other type. The passive which has the surface from of on object topicalization is not been found in the Sundanesse language and the passive sentence in the Indonesian language which the surface from of on object topicalization form. Its will always become the canonical passive form in the Sundanesse language. Keywords: passive sentence,